The Impact of Corporate Governance on Intellectual Capitals Efficiency in Indonesia - Widijaya, Widijaya; Angelica, Angelica (Budapest International Research and Critics University, 2021)
The purpose of this study is to evaluate the impact of corporate governance (board size, board independence, audit committee financial expertise, audit committee independence, and audit committee size) on intellectual capital (IC) in companies listed on the Indonesia Stock Exchange (IDX). The method used for this quantitative research to test the relation between corporate governance and intellectual capital is panel data regression by using secondary data from the 2016-2020 financial report. The number of samples are 429 companies with 2.145 observations that meet the conditions and criteria. This research shows that board independence has a significant positive effect on intellectual capital, meanwhile, board size, audit committee financial expertise, audit committee independence, and audit committee size do not affect intellectual capital. The control variable in this research shows that firm size has a significant positive effect on intellectual capital, meanwhile, leverage and return on investment do not affect intellectual capital.